Readiness of health facilities and determinants to manage diabetes mellitus: evidence from the nationwide Service Provision Assessment survey of Afghanistan, Bangladesh and Nepal. Issue 12 (30th December 2021) - Huda, Md Durrul; Rahman, Mosiur; Rahman, Md Mosfequr; Islam, Md Jahirul; Haque, Syed Emdadul; Mostofa, Md Golam
Abstract : Objectives: Using nationally representative surveys, the study's aims were to: (1) evaluate healthcare facilities' readiness to provide diabetes mellitus (DM) services and (2) identify the factors that affect DM service readiness. Data source: Data from Service Provision Assessment surveys conducted in three low-resource South Asian (SA) countries: Afghanistan, Bangladesh and Nepal, were used in this study. Design: Cross-sectional nationally representative survey Participants: A total of 117, 317 and 397 public and private health facilities in Afghanistan, Bangladesh and Nepal, respectively were analysed. Primary outcome: A total of 12 items/indicators were used to measure a health facility's readiness to provide DM services across four domains. Results: For DM management, about 39.3%, 58.4% and 58.2% of health facilities in Afghanistan, Bangladesh and Nepal centred around 7–8, 3–6 and 4–6 items. Only 12.8%, 5.0% and 4.8% of healthcare facilities in Afghanistan, Bangladesh and Nepal reported having at least % (9/12) of the necessary items for DM management, and no one reported having all 12 important items for DM management. According to the negative binomial regression models, the factors associated with higher readiness scores vary among the three countries analysed. Regression models also showed that increases in the number of DM care providers and facility types are similar factors linked to increased readiness scores in all three countries. Conclusions: In order to increase a health facility's readiness to offer DM care, country-specific factors must be addressed in addition to common factors found in all three countries. Further research is required to determine the cause of country-level differences in tracer item availability in order to develop targeted and effective country-specific strategies to improve care quality in the SA region.